A high‐precision and fast off‐line beamforming pattern estimation technique for active phased array antenna application. Issue 8 (21st May 2022) - Zhou, Zicheng; Lu, Xiaopeng; Yao, Yufan; Niu, Yang; Fang, Xin; Qiao, Xingwang; Huang, Guan‐Long; Gu, Changqing
Abstract: A detailed modeling method including all states of each active devices is proposed in this work, aiming to achieve high‐precision and fast off‐line estimation of beamforming pattern. Experimental verification of hundreds of radiating patterns shows that the beam steering angle accuracy is able to obtain 0.2% (Tx mode) and 0.19% (Rx mode) beam width in average, respectively; and the beam width accuracy is 0.2% (Tx mode) and 0.39% (Rx mode) in average, respectively. Also, SLL accuracy can reach 0.01 dB (Tx mode) and 0.1 dB (Rx mode), respectively. By adopting this technology, the optimal beam controlling codes of large active phased array antenna (APAA) could be quickly derived. Furthermore, measurement and online compensation works of enormous quantities of beams could be greatly simplified.